Dlaczego warto odróżniać sufiks od końcówki? (na marginesie artykułu Marka Stachowskiego "Terminy „sufiks” i „końcówka” w polskiej terminologii gramatyczne j") - Wanda Fijałkowska (Ksiegarnia Akademicka Publishing, 2019)
Why is the Distinction between Suffix and Desinence Worth Preserving? (a reply to M. Stachowski’s paper The terms “suffix” and “desinence” among Polish grammatical terms) This paper is an answer to M. Stachowski’s article The terms “suffix” and “desinence” among Polish grammatical terms; it presents a different point of view. It points out that the terms mentioned in the title are not only used separately within the sub-disciplines of morphology, i.e. in research concerning inflection and word-formation, but also, due to their functions, make possible the distinction between lexicon and syntax, as well as the structuring of the lexicon. They also play a role in glottodidactics. An analysis of some derivatives, coupled with an interpretation of the terms extracted from linguistic compendia concerning Polish and French, shows that the distinction between a suffix and a desinence is both simple and useful. The attributes of a suffix are: 1) changing the meaning of the base; 2) absence of changes during inflection; 3) position before the ending (desinence). The second of the analysed terms does not possess these properties.